1959
DOI: 10.1002/cber.19590921007
|View full text |Cite
|
Sign up to set email alerts
|

Ungewöhnlich verlaufende Oxydationen mit Perjodsäure, I

Abstract: HESE und MIX 2421 eintritt, und anschliel3end auf dem Wasserbade erwarmt. Die rnit Alkohol entfirbte und filtrierte UIsung wird unter Einleiten von COz auf dem Wasserbade eingeengt, angesauert und erschbpfend ausgeithert. Die Tricarbonsiiure kristallisiert beim Anreiben mit Athylacetat/Benzol und wird aus Acetonitril umkristallisiert. Schmp. 21 1-212". C9Hlz06 (216.2) Ber. C 49.99 H 5.59 Gef. C 49.97 H 5.70 &quiv.-Gew. 73.0 cis-3-Methyl-cyclopentan-tricarbonsdure-(l cis. 2trans.4cis) : I1 wird wie I mit Perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1962
1962
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Hesse and Mix had demonstrated that carbon-carbon double bonds are cleavable by periodate if at least one carbon is substituted by a free hydroxyl group and if the double bond is in coGugation with a carbonyl group (44). The oxidation of 22 by periodate could thus be postulated to proceed as depicted in Scheme 5 without intention to dzferentiate between homolytic and heterolytic processes or to show actual hydration states of the iodine compounds.…”
Section: G28m38n207mentioning
confidence: 99%
See 1 more Smart Citation
“…Hesse and Mix had demonstrated that carbon-carbon double bonds are cleavable by periodate if at least one carbon is substituted by a free hydroxyl group and if the double bond is in coGugation with a carbonyl group (44). The oxidation of 22 by periodate could thus be postulated to proceed as depicted in Scheme 5 without intention to dzferentiate between homolytic and heterolytic processes or to show actual hydration states of the iodine compounds.…”
Section: G28m38n207mentioning
confidence: 99%
“…In view of the great variability of the dihedral angles in five-membered rings, and hence of the corresponding coupling constants (46-481, the problem of stereochemical assignments was thought to be resolvable by comparison of coupling constants after increasing conformational rigidity of goldinamine by introduction of a 1,3-dioxolane ring and by selecting model tetrahydrofurans with substituents closely approximating those of O-isopropylidene-N-(2,4-dinitrophenyl)goldinamine (4-bromobenzyl) ether (44). Thus, four model substances 55-58 ( …”
Section: G28m38n207mentioning
confidence: 99%
“…Examples are uscharine (IV) (Hesse and Mix, 1959) and its dihydroderivative voruscharine (Hesse and Ludwig, 1960) which occur in the latex IV of Calotropis procera. These compounds do not appear to have seen clinical trial but uscharine has been shown to have a potency 58 per cent of that of ouabain in the etherised cat (Chen, Bliss and Robbins, 1942).…”
Section: Discussionmentioning
confidence: 99%
“…In aprotic so lvents co ntainin g so me wate r , periodic acid has bee n used for the oxidative hydroxylati o n of an active me thylene group [34][35][36] , for oxidative cleavage of e nols and reductones [37,38 ] , and for hydroxylation and further oxidation of co mpounds co ntaining an isolated double bond , e.g., cinnami c acid [39] and c holesterol [40] .…”
mentioning
confidence: 99%